Indigenous healers in the North West province: A survey of their clinical activities in health care in the rural areas - S. N. Shai-Mahoko (AOSIS, 1996)
The purpose of this study was to explore the clinical conditions brought to indigenous healers by people in the rural areas in search of health care. The demographic variables and preventive, promotive, curative and follow-up activities of indigenous healers were investigated. Data were collected from a simple random sample of 35 indigenous healers. A questionnaire designed by Mogoba (1984) for investigation of training and functioning of traditional doctors in Southern Africa was modified and used to collect data.